2016
DOI: 10.1177/1420326x16659326
|View full text |Cite
|
Sign up to set email alerts
|

Retrofitting public spaces for thermal comfort and sustainability

Abstract: This article discusses the retrofitting of public spaces in compact urban areas bearing in mind the need for outdoor thermal comfort. The role of paving materials and vegetation was focused on a field survey undertaken at a square in Porto, Portugal. The potential for microclimatic improvement of different combinations of paving materials and vegetation was explored through simulations with ENVI-met. The options, objectives and results of the simulations and an evaluation of Life Cycle Assessment related facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…This study was followed by Klemm and colleagues (Klemm et al 2015a;Klemm et al 2015b;Klemm et al 2017) who indicated psychological effects of green elements on thermal perception that cannot be related to measurable biometeorological effects. Soon after, Cortesão studied building materials in urban plazas (Cortesão et al 2016), and Krüger et al thermal perception in different street typologies (Krüger 2017). Shih and colleagues studied spatial elements in Taiwanese school yards (Shih et al 2017), Peng et al the spatial environment in different urban Dutch public spaces (Peng et al 2019), and Yung et al in Hong Kong gardens (Yung et al 2019).…”
Section: Reshaping the Existing Modelmentioning
confidence: 99%
“…This study was followed by Klemm and colleagues (Klemm et al 2015a;Klemm et al 2015b;Klemm et al 2017) who indicated psychological effects of green elements on thermal perception that cannot be related to measurable biometeorological effects. Soon after, Cortesão studied building materials in urban plazas (Cortesão et al 2016), and Krüger et al thermal perception in different street typologies (Krüger 2017). Shih and colleagues studied spatial elements in Taiwanese school yards (Shih et al 2017), Peng et al the spatial environment in different urban Dutch public spaces (Peng et al 2019), and Yung et al in Hong Kong gardens (Yung et al 2019).…”
Section: Reshaping the Existing Modelmentioning
confidence: 99%
“…Public open spaces are very important for everyday living because all civic, cultural, and social activities occur there. Previous researches showed that outdoor thermal comfort directly affects the intensity of use of public open spaces and outdoor activities [20,21], and that spatial characteristics as the form, configuration and combination of surface materials influence the urban microclimate [22]. The urban climate and outdoor thermal comfort can be improved by adopting cooling strategies.…”
Section: S990mentioning
confidence: 99%
“…In the tropics, the application of natural elements is key to formulating mitigation measures as a replacement to hard surfaces and treatment of anthropogenic emissions (Duarte, Shinzato, Gusson, & Alves, 2014). Thereby, application of design elements such as vegetation and water features take advantage of existing structure and thus contribute to the microclimate of the open spaces (Cortesao et al, 2016). As studied by Anupriya (2016), the microclimatic condition of the urban atmosphere is very much affected by development and congested composition of the urban landscape, which significantly causes thermal discomfort to the surrounding occupants.…”
Section: Application Of Natural Elements For Natural Cooling In Open mentioning
confidence: 99%
“…The presence of vegetation contributes to natural cooling by providing shade and ventilation. (Abdulkareem, 2015;Altinisik et al, 2014;Anupriya, 2016;Cortesao et al, 2016;Duarte et al, 2014;Gómez-Muñoz et al, 2010;Hsieh et al, 2016;Jamei et al, 2016;Perini & Magliocco, 2014;Qaid et al, 2016;Thani et al, 2012) These design requirements indicated for the tropics may not be applicable for cold climates as it may create adverse effects. The design requirements for optimum thermal performance of open spaces are manifested not only in the need to reduce heat gains/losses but also to counterbalance the effects of climate changes.…”
Section: Analysis and Findingsmentioning
confidence: 99%
See 1 more Smart Citation